Controlled whey protein hydrolysis using two alternative proteases - Pintado, Manuela E. (2011)
Whole whey was hydrolyzed for 12 h with Protease 2A and Trypsin using two concentrations of enzyme (20 and 40 g/kgprotein). Samples were assayed for total viable counts of adventitious microflora that survived thermization, total acidity, total concentration of free amino acids, peptide profile and overall degree of hydrolysis. The highest total concentration of free amino acids was observed when hydrolysis was effected by Protease 2A, and the major variations in amino acid qualitative composition occurred between 2 and 6 h: Leu exhibited the most significant increase, followed by Lys, Phe and Ile. Hydrolysis with Trypsin led to release of high amounts of Lys. Quantitative depletion of β-lactoglobulin was observed by 2 h under all processing conditions, and hydrolysis of α-lactalbumin was slower when Trypsin was employed. Formation of peptides was more extensive under the action of Trypsin than of Protease 2A, and the major peptides released by the former had molecular weights mainly in the ranges 7500–8000 and 4000–4500 Da, whereas those released by the latter accumulated in the range 7000–7500 Da. The differences between the hydrolytic actions of Trypsin and Protease 2A were significant except with respect to the concentration of Glu, as well as degree of breakdown of immunoglobulin G and β-lactoglobulin. Growth of adventitious bacteria and generation of free amino acids were successfully modeled using postulated mathematical models. The values of vmax for Trypsin were 0.15 and 0.06 g/(l h) for 40 and 20 g/kgprotein, respectively, and for Protease 2A were 0.86 and 0.50 g/(l h) for 40 and 20 g/kgprotein, respectively.